Snakes And Ladders Game (SMENA) to Improve Knowledge And Readiness For Menarche Among Elementary School Girls: A Community Service Program (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Menarche is a natural biological process that often causes anxiety and confusion among elementary school girls due to a lack of education before their first menstruation. At the concrete operational stage of development, children require interactive and enjoyable learning methods to optimally understand information. This community service program aimed to improve knowledge and readiness for menarche among 30 fifth-grade female students at SDN 1 Nyantong. Before the intervention, participants completed a pretest questionnaire. The intervention used a modified Snakes and Ladders game (SMENA), followed by a posttest to assess changes in knowledge and readiness for menarche. The analysis showed that the average knowledge score increased from 27.4 in the pretest to 29.3 in the posttest, with a p-value of 0.002 using the Wilcoxon Signed Rank Test, indicating a significant improvement in knowledge and readiness. Qualitative observations revealed 100% student participation, a threefold increase in the number of questions asked, and high learning enthusiasm throughout the intervention. In conclusion, the SMENA game effectively improved knowledge and readiness for menarche among elementary school girls and is recommended for replication using a train-the-trainer approach for teachers, particularly in public elementary schools with limited health education resources.